'When you haven't got much of a voice': an evaluation of the quality of Independent Mental Health Advocate (IMHA) services in England. (5th December 2014) - Newbigging, Karen; Ridley, Julie; McKeown, Mick; Machin, Karen; Poursanidou, Konstantina
Abstract Advocacy serves to promote the voice of service users, represent their interests and enable participation in decision‐making. Given the context of increasing numbers of people detained under the Mental Health Act and heightened awareness of the potential for neglect and abuse in human services, statutory advocacy is an important safeguard supporting human rights and democratising the social relationships of care. This article reports findings from a national review of Independent Mental Health Advocate (IMHA) provision in England. A qualitative study used a two‐stage design to define quality and assess the experience and impact of IMHA provision in eight study sites. A sample of 289 participants – 75 focus group participants and 214 individuals interviewed – including 90 people eligible for IMHA services, as well as advocates, a range of hospital and community‐based mental health professionals, and commissioners. The research team included people with experience of compulsion. Findings indicate that the experience of compulsion can be profoundly disempowering, confirming the need for IMHA. However, access was highly variable and more problematic for people with specific needs relating to ethnicity, age and disability. Uptake of IMHA services was influenced by available resources, attitude and understanding of mental health professionals, as well as the organisation of IMHA provision. Access could be improved through a system of opt‐out as opposed to opt‐in. Service user satisfaction was most frequently reported in terms of positive experiences of the process of advocacy rather than tangible impacts on care and treatment under the Mental Health Act. IMHA services have the potential to significantly shift the dynamic so that service users have more of a voice in their care and treatment. However, a shift is needed from a narrow conception of statutory advocacy as safeguarding rights to one emphasising self‐determination and participation in decisions about care and treatment.